The Effect of Heating Method on Phenolic and Flavonoid Content and Antioxidant Activity of Velvet Bean (Mucuna pruriens var. utilis) - Chaovanalikit, Arusa; Nudnim, Potjana; Mingyai, Sukanya; Ketjarut, Soraya; Potaros, Treesin; Prempiyakit, Wararat (Journal of Food Technology, Siam University, 2024)
This research aims to study the effects of different heating methods (boiling, steaming, roasting) on the phenolic content, flavonoids, and antioxidant capacity of various parts of velvet beans (pods, seeds, and seed coats). Velvet beans have 24.58% protein, 4.12% fat, 56.09% carbohydrates, 1.15% crude fiber, and 4.04% ash. The proportions of pods, seeds, and seed coats are 75:18.71:9.86% by fresh weight. The phenolic content in pods, seeds, and seed coats is 2443.70, 2089.08, and 1692.46 mg GAE/100g, respectively. The flavonoid content in pods, seeds, and seed coats is 250.27, 24.73, and 243.99 mg QE/100g, respectively. The antioxidant capacity in pods, seeds, and seed coats is 1.62, 2.16, and 4.43 (IC50 mg GAE), respectively. The highest phenolic and flavonoid contents are found in pods, resulting in the highest antioxidant capacity. Seeds have higher phenolic content compared to seed coats, resulting in higher antioxidant capacity despite seed coats having higher flavonoid content. Regarding the heating methods (boiling, steaming, roasting) applied to velvet beans, significant statistical increases (p≤0.05) in flavonoid content were observed, but no significant effects was found on phenolic content and antioxidant capacity.